Soutpansberg Mountain: a spider hotspot in the Limpopo Province of South Africa (Arachnida, Araneae) - Ansie S. Dippenaar-Schoeman; T. Caswell Munyai; Colin S. Schoeman; Norbert Hahn; Stefan H. Foord (African Invertebrates)
The Soutpansberg Mountain (SM) range in the northern part of the Limpopo Province within the Vhembe Biosphere Reserve, is a refuge for high diversity of organisms due to its geological history and location. As part of the South African National Survey of Arachnida (SANSA), the spider diversity of the Soutpansberg Mountain was determined over 27 years: 58 families, 293 genera, and 585 species were recorded. The Salticidae with 85 species, followed by Thomisidae (81 species), Araneidae, and Gnaphosidae, with 45 species each, are the most species-rich, while 11 families are represented by single species. Global distributions, endemicity, and conservation assessment are provided for each species using IUCN criteria. Most species (516, 88.1%) are widely distributed with no known threats and are of Least Concern, whereas eight species (1.4%) are of special concern. Of these, five species are Rare and one each is Critically Rare, Vulnerable, and Near Threatened. Twenty-five new species have been described from the SM since 1997, but 17 species (2.9%) are still Data Deficient, and 44 species were not evaluated due to unresolved taxonomy. The SM represents a spider biodiversity hotspot in the Limpopo Province, representing 25.4% of the total spider fauna of South Africa and 64.3% of the known spider fauna of the Limpopo Province.